Brzmienie Ulic nędzy - Bitka, Stanisław (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The article focuses on the soundtrack of Martin Scorsese’s Mean Streets, with a particular emphasis on the music of The Rolling Stones. The author argues that this is the first film in which Scorsese fully establishes his distinctive directorial style, characterized by the use of pre-existing music as an integral narrative device. Deeply rooted in the film’s diegesis, the music becomes a crucial component of the storytelling. Through an audiovisual analysis of selected tracks, the author demonstrates that the soundtrack, operating through contrasts, plays a key role in the character development and highlights the film’s central issues, such as moral ambivalence, violence, and the tension between tradition and modernity.